Привет!
Ответ:
а) -90x⁵y⁷
б) 2x² + 8xy
Пошаговое объяснение:
а) 10x²y ⋅ (-3xy²)³ = 10x²y ⋅ (-9x³y⁶) = -90x⁵y⁷
б) (x + 4y)² - (4y - x)(x + 4y) = (x + 4y)(x + 4y - 4y + x) = 2x(x + 4y) = 2x² + 8xy
Надеюсь помог, удачи!
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Привет!
Ответ:
а) -90x⁵y⁷
б) 2x² + 8xy
Пошаговое объяснение:
а) 10x²y ⋅ (-3xy²)³ = 10x²y ⋅ (-9x³y⁶) = -90x⁵y⁷
б) (x + 4y)² - (4y - x)(x + 4y) = (x + 4y)(x + 4y - 4y + x) = 2x(x + 4y) = 2x² + 8xy
Надеюсь помог, удачи!